Impact of Globalization and Advanced Technologies on Online Business Models - Ho, Ree C. (IGI Global, 2021)
Online business has been growing progressively and has become the major business platform within the past two decades. The internet bulldozed the development of new business models and innovations that substantially changed the way businesses run today. This led to a growth of advanced technologies used in online business such as data analytics, machine learning, and artificial intelligence. With higher internet connectivity and the exponential growth of mobile devices, shopping processes and behaviors were significantly affected as people are consistently connected online. Consumers can easil.